Gender Differences in Prognosis and Risk Stratification of Brugada Syndrome: A Pooled Analysis of 4,140 Patients From 24 Clinical Trials - Yuan, Mengchen; Tian, Chao; Li, Xinye; Yang, Xinyu; Wang, Xiaofeng; Yang, Yihan; Liu, Nian; Kusano, Kengo F.; Barajas-Martinez, Hector; Hu, Dan; Shang, Hongcai; Gao, Yonghong; et al. (Frontiers in Physiology, 2018)
Background: Male gender has been consistently shown to be a risk factor for a greater number of arrhythmic events in patients with Brugada Syndrome (BrS). However, there have been no large-scale comprehensive pooled analyses to statistically and systematically verify this association. Therefore, we conducted a pooled analysis on gender differences in prognosis and risk stratification of BrS with a largest sample capacity at present. Methods: We searched PubMed, Embase, Medline, Cochrane Library databases, Chinese National Knowledge Infrastructure, and Wanfang Data for relevant studies published from 2002 to 2017. The prognosis and risk stratification of BrS and risk factors were then investigated and evaluated according to gender. Results: Twenty-four eligible studies involving 4,140 patients were included in the analysis. Male patients (78.1%) had a higher risk of arrhythmic events than female patients (95% confidence interval: 1.46–2.91, P<0.0001). Among the male population, there were statistical differences between symptomatic patients and asymptomatic patients (95% CI: 2.63–7.86, P<0.00001), but in the female population, no statistical differences were found. In the female subgroup, electrophysiological study (EPS) positive patients had a tendency toward a higher risk of arrhythmic events than EPS-negative patients (95% CI: 0.93–29.77, P=0.06). Conclusions: Male patients are at a higher risk of arrhythmic events than female patients. Within the male population, symptomatic patients have a significantly higher risk profile compared to asymptomatic patients, but no such differences are evident within the female population. Consequently, in the female population, the risk of asymptomatic patterns cannot be underestimated.